Strong-field QED effects on polarization states in dipole and quadrudipole pulsar emissions - Dong-Hoon Kim; Chul Min Kim; Sang Pyo Kim (European Physical Journal C: Particles and Fields)
Abstract Highly magnetized neutron stars have quantum refraction effects on pulsar emission due to the non-linearity of the quantum electrodynamics (QED) action. In this paper, we investigate the evolution of the polarization states of pulsar emission under the quantum refraction effects, combined with the dependence on the emission frequency, for dipole and quadrudipole pulsar models; we solve a system of evolution equations of the Stokes vector, where the birefringent vector, in which such effects are encoded, acts on the Stokes vector. At a fixed emission frequency, depending on the magnitude of the birefringent vector, dominated mostly by the magnetic field strength, the evolution of the Stokes vector largely exhibits three different patterns: (i) monotonic, or (ii) half-oscillatory, or (iii) highly oscillatory behaviors. These features are understood and confirmed by means of approximate analytical solutions to the evolution equations. Also, the evolution patterns are shown to differ between dipole and quadrudipole pulsar models, depending on the magnetic field strength.